Angiotensin-converting enzyme inhibition studies by natural leech inhibitors by capillary electrophoresis and competition assay. - Deloffre, L; Sautiere, P; Huybrechts, R; Hens, K; Vieau, D; Salzet, M (2004)
A protocol to follow the processing of angiotensin I into angiotensin II by rabbit angiotensin-converting enzyme (ACE) and its inhibition by a novel natural antagonist, the leech osmoregulator factor (LORF) using capillary zonal electrophoresis is described. The experiment was carried out using the Beckman PACE system and steps were taken to determine (a) the migration profiles of angiotensin and its yielded peptides, (b) the minimal amount of angiotensin II detected, (c) the use of different electrolytes and (d) the concentration of inhibitor. We demonstrated that LORF (IPEPYVWD), a neuropeptide previously found in leech brain, is able to inhibit rabbit ACE with an IC(50) of 19.8 micro m. Interestingly, its cleavage product, IPEP exhibits an IC(50) of 11.5 micro m. A competition assay using p-benzoylglycylglycylglycine and insect ACE established that LORF and IPEP fragments are natural inhibitors for invertebrate ACE. Fifty-four percent of insect ACE activity is inhibited with 50 micro m IPEP and 35% inhibition with LORF (25 mm). Extending the peptide at both N- and C-terminus (GWEIPEPYVWDES) and the cleavage of IPEP in IP abolished the inhibitory activity of both peptides. Immunocytochemical data obtained with antisera raised against LORF and leech ACE showed a colocalization between the enzyme and its inhibitor in the same neurons. These results showed that capillary zonal electrophoresis is a useful technique for following enzymatic processes with small amounts of products and constitutes the first evidence of a natural ACE inhibitor in invertebrates.